2013
DOI: 10.1007/s10616-013-9563-5
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol partially reverses symptoms of diabetes in STZ-induced diabetic rats

Abstract: Little is known about the protective effects of carvacrol on the symptoms of streptozotocin induced diabetes in rats. Hence, this present study was designed to evaluate the protective effect of the strong antioxidant, carvacrol, on the symptoms of streptozotocin induced diabetes in rats. Carvacrol at the doses of 25 and 50 mg/kg body weight were orally administered to diabetic rats for a period of 7 days after the onset of diabetes. Food-water intake and body weight changes were daily recorded. Biochemical par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 28 publications
8
35
0
4
Order By: Relevance
“…The hypoglycemic effect observed may be attributed to the presence of monoterpenic phenols such as carvacrol (Deng et al, 2013;Ezhumalai et al, 2014) and/or eugenol in the essential oil (Mnafgui et al, 2013a,b;Nangle et al, 2006;Srinivasan et al, 2014). The hypoglycemic effect of carvacrol, which is the major compound identified in the studied plant, was previously demonstrated to partially reverse symptoms of diabetes in streptozotocin-induced diabetic rats (Bayramoglu et al, 2013). The previous study indicated that despite its hypoglycemic potential, carvacrol could not have insulin-mimetic properties or be capable to induce insulin production from the surviving beta cells.…”
Section: Discussionmentioning
confidence: 85%
“…The hypoglycemic effect observed may be attributed to the presence of monoterpenic phenols such as carvacrol (Deng et al, 2013;Ezhumalai et al, 2014) and/or eugenol in the essential oil (Mnafgui et al, 2013a,b;Nangle et al, 2006;Srinivasan et al, 2014). The hypoglycemic effect of carvacrol, which is the major compound identified in the studied plant, was previously demonstrated to partially reverse symptoms of diabetes in streptozotocin-induced diabetic rats (Bayramoglu et al, 2013). The previous study indicated that despite its hypoglycemic potential, carvacrol could not have insulin-mimetic properties or be capable to induce insulin production from the surviving beta cells.…”
Section: Discussionmentioning
confidence: 85%
“…Monoterpenes are obtained from essential oils and many of them have shown antioxidant activity. Carvacrol (CAR) used as the most active constituent of thyme EOs is a predominant monoterpenoic phenol and exhibits a potent anti-fungal, anti-viral, anti-tumor, antidiabetic and anti-inflammatory effect (Bayramoglu et al 2014). It is also recognized as a safe food additive and used as flavoring agent in packed foods, sweets, beverages, and chewing gum (Abdollahi et al 2012;Gilling et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Glucose in diabetic mice fails to convert to carbohydrates due to the lack of insulin. However, massive accumulation of glucose metabolizes to fatty acids in liver [ 24 ]. The overproduction of serum fatty acids by STZ-induced diabetics facilitates the conversion of excessive fatty acids into phospholipids and cholesterol in liver [ 22 ].…”
Section: Discussionmentioning
confidence: 99%